Predictive validity of post-ume scores of first year students in the Nigerian universities between 2006-2009 (2012)
The Joint Admission and Matriculation Board (JAMB) have been facing a lot of criticism due to the poor performance or poor quality of Nigerian university undergraduates. Candidates for admissions into Nigerian universities are made to undergo Post-UME screening before they are admitted into the Nigerian universities. This study was designed to investigate the Predictive Validity of Post-University Matriculation Examination of First Year Students of Nigerian Universities from 2006- 2009. The samples used were 5,846 1students from two Nigerian Universities who were admitted between 2006 and 2009 into Eight Faculties. Data were collected from the records and admissions office of the two universities used for the study. The data were subjected to analysis using Pearson's Product Moment Correlation and multiple regression analysis. The result showed that CGPA and Post-UME scores of students is positively significant to the undergraduate academic achievement Therefore, Post- UME is relevant and adequate to serve as criterion validity for performance in the university. It was recommended that the Joint Admission and Matriculation Board (JAMB) should take a deeper look into her examinations in terms of focus and emphasis vis-a-vis the actual skills and competences the universities emphasize.